RANCANG BANGUN SISTEM GENERAL DIAGNOSTIC SCANNER UNTUK MENGAKSES ECU MOBIL DENGAN KOMUNIKASI SERIAL OBD-2 - Kusumo, Yanuar Prasojo; Harianto, Harianto; Wibowo, Madha Christian (Journal of Control and Network Systems, 2015)
Embedded electronic control system applied by car manufacturers on car engines manufactured today are ECU (Electronic Control Unit). Every car brand has a different ECU. To be able to diagnose car engine damage from a variety brands of car need a cheap diagnostic scanner and compatible with many brands of car.In order for technician from not official car manufacturers workshop can make a diagnostic and repair the damage of car engines from variety brands with ease, perform realtime monitoring and can do datalogging parameter values of sensor data in the SD card when realtime monitoring process, then made a General Diagnostic Scanner system for access car ECU with OBD-2 serial communication at affordable cost.Based on the test results showed that OBD-2 serial communication along with the compatible data retrival of ECU parameters between GDS system withÂ Chevrolet estate 2009 and Ford fiesta 2012 cars ECU that consist of OBD-2 ISO 9141-2 and ISO 15765 (CAN) communication protocol can do 100% success with 7 compatible ECU parameters in Chevrolet estate and 100% success with 9 compatible ECU parameters (all parameters) in Ford fiesta. In ECU realtime monitoring testing, GDS system can do realtime monitoring with an average error 5,01% in Chevrolet estate for 7 ECU parameters and 5,86 % in Ford fiesta for 9 ECU parameters. And from damage diagnostic testing result, GDS system can do car engine damage diagnostic with success when in idle condition and when the car in running position for speed parameter in Chevolet estate and Ford fiesta cars that give warning âmelebihi batas normalâ when excedded threshold limit of normal engine cars limit which has been adapted for the consideration of testing. In datalogging testing, GDS system cannot do datalogging process and not success for save realtime monitoring data process into SDHC card.Keywords: ECU, Diagnostic, Realtime Monitoring, Datalogging, General Diagnostic Scanner.